Microstructure, method for producing the microstructure, and photoelectric conversion element

By adopting a microstructure with a multi-layer structure, which consists of a specific material and covers the surface layer of Mohstan disulfide or other transition metal disulfide, the problem that the light scattering layer in the photoelectric conversion element is difficult to suppress carrier resistance loss, and the dual optimization of light scattering and carrier resistance loss is achieved.

JP7649621B2Active Publication Date: 2025-03-21IDEMITSU KOSAN CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2019160289
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-09-03
Publication Date
2025-03-21
Estimated Expiration
2039-09-03

AI Technical Summary

Technical Problem

While suppressing optical loss, the light scattering layer of the conventional photoelectric conversion element is difficult to effectively suppress carrier resistance loss.

Method used

A microstructure with a multi-layer structure consisting of a material selected from aluminum oxide, silicon nitride, titanium oxide, hyaluronic acid wire or its multi-layer structure, the surface layer comprises an insulating core part and a surface layer covering the core part, the surface layer is made of Mosch disulfide (MoS2) or other transition metal disulfide, the core part has a dimension of 100 nm to 1200 nm and the surface layer has a thickness of 5 nm to 50 nm.

Benefits of technology

This microstructure can not only realize the light scattering function in the light scattering layer of the photoelectric conversion element, but also effectively suppress carrier resistance loss and improve photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649621000001
    Figure 0007649621000001
  • Figure 0007649621000002
    Figure 0007649621000002
  • Figure 0007649621000003
    Figure 0007649621000003
Patent Text Reader

Abstract

To provide a microstructure capable of suppressing carrier resistance loss in addition to an optical function that causes light scattering when applied to a light scattering layer of a photoelectric conversion element.SOLUTION: A microstructure (nanostructure 10) includes an insulating core portion 11, and a surface layer 12 that covers the core portion, and the surface layer is composed of a transition metal dichalcogenide. With such a configuration, when the microstructure is applied to a light scattering layer of a photoelectric conversion element, in addition to an optical function of causing light scattering, the resistance loss of the carrier can be suppressed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a microstructure, a method for manufacturing a microstructure, and a photoelectric conversion element. [Background technology]

[0002] It has been proposed to form a light scattering layer in which nanometer-scale particles (nanoparticles) are dispersed in a photoelectric conversion element, for example, in order to scatter light near the photoelectric conversion layer of the photoelectric conversion element and reduce optical loss.

[0003] As nanoparticles applicable to this type of light scattering layer, for example, nanoparticles whose surfaces are formed of an insulator having a smaller refractive index than the light absorbing layer have been proposed (see Patent Document 1). In addition, a light-scattering film has also been proposed in which a light scatterer is formed from a nano-structured insulator such as titanium oxide, diamond, or silicon oxide, and the light scatterer is embedded in a translucent and conductive medium (see Patent Document 2). Also known is a dye-sensitized solar cell that uses nanoparticles in which the surface of SiO2 particles is coated with TiO2 (see Non-Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-055178 A [Patent Document 2] JP 2006-171026 A [Non-patent literature]

[0005] [Non-Patent Document 1] “Designed Synthesis of SiO2 / TiO2 Core / Shell Structure As Light Scattering Material for Highly Efficient Dye-Sensitized Solar Cells” ACS Appl. Mater. Interfaces 2013,5, 4815-4820 Summary of the Invention [Problem to be solved by the invention]

[0006] From the viewpoint of further improving the performance of photoelectric conversion elements, in addition to the optical function of scattering light in the light scattering layer, it is desired to suppress the resistance loss of carriers in the light scattering layer.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a microstructure that, when applied to a light scattering layer of a photoelectric conversion element, can suppress the resistance loss of carriers in addition to the optical function of scattering light. [Means for solving the problem]

[0008] The microstructure according to one embodiment of the present invention comprises: The multilayer structure is composed of a material selected from the group consisting of alumina, silicon nitride, titania, and soda lime glass, or a material selected from the group consisting of silica, alumina, silicon nitride, titania, and soda lime glass. It has an insulating core and a surface layer covering the core. The surface layer is made of a transition metal dichalcogenide other than MoS2. The size of the core is 100 nm to 1200 nm, and the thickness of the surface layer is 5 nm to 50 nm. Another aspect of the present invention is The multilayer structure is composed of a material selected from the group consisting of alumina, silicon nitride, titania, and soda lime glass, or a material selected from the group consisting of silica, alumina, silicon nitride, titania, and soda lime glass.A method for manufacturing a microstructure having an insulating core and a surface layer covering the core, the surface layer being composed of a transition metal dichalcogenide other than MoS2, the core having a size of 100 nm to 1200 nm, and the surface layer having a thickness of 5 nm to 50 nm, the method includes the steps of preparing a first microstructure having an insulating surface, forming a layer containing a transition metal element on the surface of the first microstructure to form a second microstructure, and chalcogenizing the layer containing a transition metal element of the second microstructure to form a third microstructure having a surface layer of transition metal dichalcogenide. Effect of the Invention

[0009] According to the present invention, it is possible to provide a microstructure that, when applied to a light scattering layer of a photoelectric conversion element, can suppress the resistance loss of carriers in addition to the optical function of scattering light. [Brief description of the drawings]

[0010] [Figure 1] 1A and 1B are diagrams illustrating an example of the configuration of a nanostructure according to an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram showing an example of the crystal structure of a transition metal dichalcogenide. [Diagram 3] 4 is a flow chart showing an example of a method for manufacturing a nanostructure according to the present embodiment. [Figure 4] 1 is a schematic diagram showing a configuration example of a photoelectric conversion element according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment will be described with reference to the drawings. In the embodiments, in order to make the description easier to understand, structures or elements other than the main parts of the present invention will be described in a simplified or omitted manner. Also, in the drawings, the same elements are given the same reference numerals. Note that in the drawings, the shapes, dimensions, etc. of each element are shown diagrammatically and do not represent the actual shapes, dimensions, etc.

[0012] <Nanostructure configuration> FIG. 1A is a cross-sectional view that illustrates a schematic configuration example of a nanostructure 10 of this embodiment. The nanostructure 10 is an example of a minute structure, and has a nanometer-scale particle shape as a whole. The nanostructure 10 is used, for example, as a material for a light scattering layer disposed between a photoelectric conversion layer and an electrode layer of a photoelectric conversion element. The nanostructure 10 has an insulating core portion 11 and a surface layer 12 that covers the core portion 11 .

[0013] (Core 11) The core portion 11 shown in FIG. 1 is a particle made of an insulating material and has a spherical overall shape. The core portion 11 is composed of a material selected from a group of materials such as silica (refractive index 1.47), alumina (refractive index 1.76), silicon nitride (refractive index 2.0), titania (refractive index 2.49), and soda-lime glass (refractive index 1.52), or a multilayer structure whose surface is coated with any of the materials in the above group of materials. 1(B) is a cross-sectional view showing an example of a multilayer structure having an outer core portion 11a, which is a coating layer on the surface side, and an inner core portion 11b adjacent to the inner side of the outer core portion 11a. In this embodiment, an example of the core portion 11 having a two-layer structure is shown, but the core portion 11 may be a multilayer structure having three or more layers.

[0014] 1, when the core 11 is a spherical particle, the surface of the core 11 onto which light is incident becomes spherical, thereby improving the light reflection effect and light scattering effect of the nanostructure 10. In addition, by forming the surface layer 12 along the spherical surface of the core 11, it is believed that the effect of reducing the resistance loss of carriers can be improved, as described later. However, the shape of the core portion 11 and the overall shape of the nanostructure 10 are not necessarily limited to a sphere. For example, the shape of the core portion 11 and the overall shape of the nanostructure 10 may be a wire, tube, fiber, etc. on the nanometer scale.

[0015] The size of the core portion 11 is not particularly limited, but may be in the range of 100 nm to 1200 nm. For example, when the core portion 11 is a spherical particle, the particle size of the core portion 11 may be in the range of 100 nm to 1200 nm. The size of the core 11 is set according to the wavelength of the light incident on the nanostructure 10, and it is preferable that the longer the wavelength of the incident light in the intended use, the larger the upper limit of the size of the core 11. For example, when the central wavelength of the incident light in the intended use is 1000 nm, the size of the core 11 is preferably 100 nm to 1000 nm. In the above cases, when the central wavelengths are 700 nm, 450 nm, and 300 nm, respectively, the sizes of the core 11 are preferably 100 nm to 700 nm, 100 nm to 450 nm, and 100 nm to 300 nm, respectively.

[0016] FIG. 1C is a cross-sectional view showing an example of a nanostructure 10 in which a surface layer 12 is formed on the core portion 11 of the multilayer structure shown in FIG. 1B. 1(B) and (C), when the core portion 11 is a multilayer structure, when light is incident on the nanostructure 10, reflection and scattering of the light occur at the interfaces of each layer of the core portion 11. In this case, a higher light reflection effect can be achieved by making the refractive index of the outer core portion 11a, which is located on the outermost side in the core portion 11 of the multilayer structure, larger than the refractive index of the inner core portion 11b adjacent to the inner side of the outer core portion 11a.

[0017] For example, in the core portion 11 of the multilayer structure, it is preferable that the material of the outer core portion 11a covering the surface of the core portion 11 is titania (refractive index 2.49), and the material of the inner core portion 11b is silica (refractive index 1.47). With the above combination, the difference in refractive index between the outer core portion 11a and the inner core portion 11b in the core portion 11 of the multilayer structure can be increased, and the light reflection effect and light scattering effect at the interface between the outer core portion 11a and the inner core portion 11b can be increased. For example, when the nanostructure 10 is applied to the light scattering layer of a photoelectric conversion element, the above configuration can further improve the light reflection effect on the surface where the light scattering layer is arranged (for example, the back side of the light emitting surface of a light emitting element or the back side of the light receiving surface of a light receiving element).

[0018] (Surface layer 12) 1 is made of transition metal dichalcogenide (TMDC) and is a semiconductor or conductor. The surface layer 12 is capable of transmitting incident light to its inside.

[0019] A transition metal dichalcogenide is a compound having a layered structure in which a transition metal element M is bonded to a chalcogen element X and has a chemical composition of MX2. In the transition metal dichalcogenide of the surface layer 12, the transition metal element M includes at least one of V, Ta, Mo, W, Ti, Nb, Hf, and Zr, and the chalcogen element X includes at least one of S, Se, and Te.

[0020] Fig. 2 is a schematic diagram of the crystal structure of a transition metal dichalcogenide having a layered structure, which corresponds to the state of the crystal structure viewed from a direction in the ab plane intersecting with the layering direction (c-axis direction). In the case of transition metal dichalcogenides, when the layers have a layered structure, the monolayers are layered in the c-axis direction, and each layer is bonded by weak van der Waals forces. Therefore, in transition metal dichalcogenides, the resistivity in the ab plane of each layer is lower than the resistivity in the c-axis direction, which is the direction of the layers.

[0021] In this embodiment, it is preferable to form the surface layer 12 with an orientation in which the c-axis of the transition metal dichalcogenide is perpendicular to the surface of the core portion 11. This allows carriers to move in the ab-plane of the transition metal dichalcogenide along the surface of the core portion 11 in the surface layer 12 of the nanostructure 10. Since the resistivity in the ab-plane is lower than that in the c-axis direction in the stacking direction, it is believed that the resistance loss of carriers moving in the surface layer 12 of the nanostructure 10 can be reduced. Although not particularly limited, for example, in a transition metal dichalcogenide in which the transition metal element M includes at least one of Mo, W, Hf, and Zr, it is preferable to form the surface layer 12 with an orientation in which the c-axis of the transition metal dichalcogenide is perpendicular to the surface of the core portion 11.

[0022] Furthermore, when the transition metal element M of the transition metal dichalcogenide contains at least one of Nb, V, Ta, and Ti, the resistivity is lower than when it does not contain these elements, and the resistive loss of carriers in the surface layer 12 can be further reduced.

[0023] Therefore, when the transition metal element M of the transition metal dichalcogenide contains at least one of Nb, V, Ta, and Ti, the surface layer 12 does not have to be formed with an orientation such that the c-axis of the transition metal dichalcogenide is perpendicular to the surface of the core portion 11. In other words, when the transition metal element M of the transition metal dichalcogenide contains at least one of Nb, V, Ta, and Ti, the surface layer 12 may be formed such that the c-axis of the transition metal dichalcogenide is oriented randomly or in an arbitrary direction with respect to the surface of the core portion 11.

[0024] Here, when the transition metal element M contains at least one of Nb, V, Ta, and Ti, it is preferable to use (M,Mo)(Se,S)2, M(Se,S)2, MSe2, or MS2 (wherein M is any of Nb, V, Ta, and Ti). The above transition metal dichalcogenides are materials with high work functions and low resistivities.

[0025] Generally, when the surface layer 12 is formed to be thin, it becomes easier to form the surface layer 12 with an orientation in which the c-axis of the transition metal dichalcogenide is perpendicular to the surface of the core portion 11. Therefore, although not particularly limited, the thickness of the surface layer 12 of the nanostructure 10 is preferably 5 nm to 50 nm, and more preferably 30 nm or less. In addition, when the c-axis of the transition metal dichalcogenide is oriented perpendicular to the surface of the core portion 11, the resistivity of the surface layer 12 is low. Therefore, in this case, the thickness of the surface layer 12 may be a thickness equivalent to several atomic layers.

[0026] For example, assume that the above-mentioned nanostructure 10 is applied to a light scattering layer disposed between a photoelectric conversion layer and an electrode layer of a photoelectric conversion element, and the electrode layer facing the light scattering layer is the hole transport side. In this case, the surface layer 12 of the transition metal dichalcogenide of the nanostructure 10 has a work function larger than that of the photoelectric conversion layer, and the surface layer 12 of the nanostructure 10 forms an ohmic junction with the photoelectric conversion layer.

[0027] For example, when the photoelectric conversion element is a light receiving element, holes generated in the photoelectric conversion layer are transported to the electrode layer without generating a barrier. For example, when the photoelectric conversion element is a light emitting element, holes injected from the electrode are transported to the photoelectric conversion layer without generating a barrier.

[0028] Moreover, it is preferable that the refractive index of the surface layer 12 of the nanostructure 10 is greater than the refractive index of the core portion 11. This makes it possible to increase the light reflection effect at the interface between the surface layer 12 and the core portion 11 of the nanostructure 10, thereby enabling the amount of reflected light from the nanostructure 10 to be increased.

[0029] For example, when the material of the surface layer 12 is MoSe2, the refractive index is 3.25, and when the material is MoS2, the refractive index is 4.0. On the other hand, when the material of the core portion 11 is any one of silica, alumina, silicon nitride, titania, and soda-lime glass, the refractive index of the core portion 11 is in the range of 1.47 to 2.49. Therefore, it can be seen that the refractive index of the surface layer 12 can be made larger than that of the core portion 11.

[0030] <Method of manufacturing nanostructures> Hereinafter, the method for manufacturing the nanostructure 10 of this embodiment will be described with reference to the flow chart of FIG.

[0031] (Step S1) In step S1, a first nanostructure having an insulating surface is prepared. The first nanostructure corresponds to the above-mentioned core portion 11, and may be, for example, a nanoparticle made of a material such as silica, alumina, silicon nitride, titania, or soda-lime glass, or a multilayer structure whose surface side is covered with any of the above materials. Such nanoparticles may be commercially available (for example, https: / / www.sigmaaldrich.com / japan / materialscience / nano-materials / nanopowders.html reference).

[0032] (Step S2) Next, in step S2, a layer containing a transition metal element M such as molybdenum is formed on the surface of the first nanostructure to form a second nanostructure. The transition metal element M contains at least one of V, Ta, Mo, W, Ti, Nb, Hf, and Zr. Furthermore, by making the thickness of the layer containing a transition metal on the surface of the first nanostructure 30 nm or less, a surface layer 12 of transition metal dichalcogenide can be formed with an orientation in which the c-axis is perpendicular to the surface of the core portion 11 of the nanostructure 10, which is preferable.

[0033] For example, when forming a layer containing a transition metal on the first nanostructure in step S2, a barrel-type sputtering deposition device (barrel sputtering) can be used, which deposits the layer while rotating a barrel containing the first nanostructure. This allows the first nanostructure to be coated with a film containing a transition metal uniformly and efficiently.

[0034] When forming a layer containing a transition metal element on the surface of the first nanostructure by sputtering, a sputtering source containing Nb can be used. Alternatively, a sputtering source containing, for example, Mo as a transition metal element other than Nb may be used together with a sputtering source containing Nb. In this case, a layer containing Nb and Mo as transition metal elements can be formed on the surface of the first nanostructure.

[0035] In step S2, the first nanostructure may be mixed with a solution containing a transition metal element and then dried, thereby forming a second nanostructure having a layer containing a transition metal element on the surface of the first nanostructure.

[0036] In this case, the solution containing the transition metal element preferably contains Mo or W. For example, the solution may contain ammonium thiomolybdate ((NH4)2MoS4), ammonium thiotungstate ((NH4)2WS4), or a hydrate thereof. The solution containing the transition metal element may also contain sulfur, selenium, or tellurium (Te). In addition, when the solution contains sulfur, selenium or tellurium, even if the second nanostructure is heated in an atmosphere not containing chalcogen elements in step S3 described below, a nanostructure 10 (third nanostructure) having a surface layer 12 of transition metal dichalcogenide on the surface of the first nanostructure can be formed.

[0037] (Step S3) Next, in step S3, the layer containing the transition metal element in the second nanostructure is chalcogenized, thereby forming a nanostructure 10 (third nanostructure) in which a surface layer 12 of transition metal dichalcogenide is formed on the surface of the first nanostructure.

[0038] In step S3, the second nanostructure is heat-treated in an atmosphere containing a chalcogen element. When selenization is performed as the chalcogenization, a process of heating the second nanostructure is performed in an atmosphere of a selenium source gas containing selenium (e.g., hydrogen selenide or selenium vapor). When sulfurization is performed as the chalcogenization, a process of heating the second nanostructure is performed in an atmosphere of a sulfur source gas containing sulfur (e.g., hydrogen sulfide or sulfur vapor). The second nanostructure may be heated in an atmosphere containing tellurium. The second nanostructure may also be heated in an atmosphere containing multiple chalcogen elements. The heating temperature in these heat treatments is, for example, about 500°C.

[0039] For example, by selecting a transition metal element M containing at least one of Nb, V, Ta, and Ti and selenium or sulfur as the atmosphere containing the chalcogen element, a surface layer 12 of a transition metal dichalcogenide such as (M,Mo)(Se,S)2, M(Se,S)2, MSe2, or MS2 (wherein M is any of Nb, V, Ta, and Ti) can be formed.

[0040] If a layer containing a transition metal element M is formed using a solution containing sulfur, selenium or tellurium in step S2, the second nanostructure may be heated in an atmosphere not containing chalcogen elements in step S3. In this case, since the layer containing the transition metal element M already contains a chalcogen element, a nanostructure 10 having a surface layer 12 of transition metal dichalcogenide on the surface of the first nanostructure can be formed.

[0041] In addition, the heating process of the second nanostructure in step S3 is preferably performed in an atmosphere containing hydrogen. For selenization or sulfurization, it is particularly preferable to use hydrogen selenide or hydrogen sulfide, and if these gases are not used, it is preferable to include hydrogen in the atmospheric gas. When heating in an atmosphere containing hydrogen, transition metal dichalcogenide can be formed at a lower temperature than when chalcogenization is performed in an atmosphere not containing hydrogen. The heating temperature when heating in an atmosphere containing hydrogen is, for example, 420°C to 500°C. Through the above steps, the nanostructure 10 shown in FIG. 1(A) or FIG. 1(C) is completed.

[0042] <Configuration of photoelectric conversion element> Next, a configuration example of a photoelectric conversion element using the nanostructure 10 of this embodiment will be described. FIG. 4A is a cross-sectional view in the thickness direction showing an example of the configuration of a light receiving element 20A using the nanostructure 10. As shown in FIG. The light receiving element 20A is an example of a photoelectric conversion element, and examples thereof include a photosensor, a solar cell, and an imaging element.

[0043] The light receiving element 20A shown in FIG. 4(A) has a substrate 21, a first electrode layer 22, a photoelectric conversion layer 23A, and a second electrode layer 24. On the substrate 21, the first electrode layer 22, the photoelectric conversion layer 23A, and the second electrode layer 24 are laminated in this order from the bottom in the figure. The first electrode layer 22 is located on the back side of the light receiving surface, and the second electrode layer 24 is made of a transparent conductive film and faces the light receiving surface side at the top in the figure. Note that, although FIG. 4(A) shows an example in which the substrate 21 is disposed on the back side of the light receiving surface, a transparent substrate having translucency may be disposed on the second electrode layer 24 side of the light receiving surface instead of the substrate 21.

[0044] The material of the photoelectric conversion layer 23A of the light receiving element 20A can be a VI group semiconductor, a I-III-VI2 group compound semiconductor, a I2-II-IV-VI4 group compound semiconductor, a II-VI group compound semiconductor, a III-V group compound semiconductor, or an organic semiconductor.

[0045] Furthermore, a plurality of nanostructures 10 of the above embodiment are disposed at the interface of the photoelectric conversion layer 23A with the first electrode layer 22. A duplicated description of the configuration of the nanostructure 10 will be omitted. The surface layer 12 of the nanostructure 10 is in electrical contact with the first electrode layer 22. Furthermore, the photoelectric conversion layer 23A and the surface layer 12 of the nanostructure 10 form a good ohmic junction.

[0046] Photoelectric conversion layer 23A, on its surface facing first electrode layer 22 (the side opposite to the light-receiving surface), has both a portion in contact with nanostructure 10 and a portion in contact with first electrode layer 22. In other words, first electrode layer 22, on its surface facing photoelectric conversion layer 23A, has both a portion in contact with nanostructure 10 and a portion in contact with photoelectric conversion layer 23A.

[0047] As a result, the surface layer 12 of the nanostructure 10 and the first electrode layer 22 form a finely uneven surface having electrical conductivity at the interface with the photoelectric conversion layer 23A. In the light-receiving element 20A of this embodiment, the surface layer 12 of the nanostructure 10 and the first electrode layer 22 both form a conductive junction interface, which functions to transport carriers. Therefore, carriers generated in the photoelectric conversion layer 23A of the light receiving element 20A can reach the first electrode layer 22 also through the transition metal dichalcogenide in the surface layer 12 without detouring the nanostructure 10. Therefore, the resistance loss of carriers from the photoelectric conversion layer 23A to the first electrode layer 22 can be reduced.

[0048] Here, when insulating nanoparticles are disposed between the first electrode layer 22 and the photoelectric conversion layer 23A, the surface of the insulating nanoparticles does not have electrical conductivity, so that only the portion where the photoelectric conversion layer 23A and the first electrode layer 22 are in direct contact with each other becomes the junction interface. In other words, when insulating nanoparticles are disposed between the first electrode layer 22 and the photoelectric conversion layer 23A, the area of ​​the junction interface with the photoelectric conversion layer 23A becomes smaller and the resistance loss of carriers also becomes larger, compared to the light receiving element 20A shown in FIG. 4(A).

[0049] Light is incident on the light receiving element 20A from the light receiving surface side. The light incident on the light receiving element 20A passes through the second electrode layer 24 and reaches the photoelectric conversion layer 23A, and part of the light also reaches the nanostructure 10 and the first electrode layer 22.

[0050] A part of the light that reaches the surface layer 12 of the nanostructure 10 is reflected by the surface of the surface layer 12 and enters the photoelectric conversion layer 23A again. The rest of the light that reaches the surface layer 12 of the nanostructure 10 is incident on the surface layer 12. A part of the light that enters the surface layer 12 of the nanostructure 10 is absorbed by the surface layer 12, but the rest reaches the interface between the surface layer 12 and the core portion 11. The light is reflected and scattered on the surface of the core portion 11, and the reflected light enters the surface layer 12 again, and further the light is scattered at the interface between the surface layer 12 and the photoelectric conversion layer 23A. The light that enters the core portion 11 also reaches the interface between the core portion 11 and the surface layer 12 again, except for the light that is absorbed by the core portion 11, and causes reflection and scattering.

[0051] In this manner, light is reflected or scattered at the interface between the surface layer 12 and the core portion 11 of the nanostructure 10, and the reflected light from the rear side of the light receiving surface of the light receiving element 20A increases. This increases the amount of light absorbed by the photoelectric conversion layer 23A, thereby reducing the optical loss of the light receiving element 20A.

[0052] 4(B) is a cross-sectional view in the thickness direction showing a configuration example of a light-emitting element 20B using the nanostructure 10. The light-emitting element 20B is an example of a photoelectric conversion element, and examples of the light-emitting element include an LED (light emitting diode), an organic EL (electro-luminescence) element, and an inorganic EL element.

[0053] The light-emitting element 20B shown in FIG. 4(B) has a substrate 21, a first electrode layer 22, a photoelectric conversion layer 23B, and a second electrode layer 24. On the substrate 21, the first electrode layer 22, the photoelectric conversion layer 23B, and the second electrode layer 24 are laminated in this order from the bottom in the figure. The first electrode layer 22 is located on the back side of the light-emitting surface, and the second electrode layer 24 is made of a transparent conductive film and faces the light-emitting surface side, which is the upper side in the figure. Note that, although FIG. 4(B) shows an example in which the substrate 21 is disposed on the back side of the light-emitting surface, a transparent substrate having translucency may be disposed on the second electrode layer 24 side of the light-emitting surface instead of the substrate 21.

[0054] In addition, a plurality of nanostructures 10 of the above embodiment are arranged at the interface between the photoelectric conversion layer 23B and the first electrode layer 22. The configuration and arrangement of the nanostructures 10 are similar to those in the case of the light receiving element 20A of FIG.

[0055] In the light emitting element 20B, a voltage is applied between the first electrode layer 22 and the second electrode layer 24 to inject carriers into the photoelectric conversion layer 23B, where the carriers recombine to emit light. At this time, in the first electrode layer 22 in which the nanostructure 10 is arranged, carriers are injected not only through the first electrode layer 22 but also through the surface layer 12 of the nanostructure 10, so that resistance loss is reduced.

[0056] In addition, in the light-emitting element 20B, a portion of the light emitted in the photoelectric conversion layer 23B toward the first electrode layer 22 enters the nanostructure 10, and is reflected or scattered on the surface of the surface layer 12 or at the interface between the surface layer 12 and the core portion 11, and is directed toward the light-emitting surface. This allows the amount of light emitted from the light emitting surface side to be increased by the nanostructure 10, thereby reducing optical loss in the light emitting element 20B.

[0057] In addition, when the difference in refractive index between the first electrode layer 22 and the photoelectric conversion layer (23A, 23B) in the photoelectric conversion element is small, the reflectance at the interface between them is small. In particular, when the nanostructure 10 is used in a photoelectric conversion element having such specifications to increase the reflected light from the back side of the light receiving surface or the back side of the light emitting surface, the effect of reducing optical loss becomes greater. The optical absorption coefficient of the core 11 of the nanostructure 10 is preferably smaller than that of the surface layer 12 and the photoelectric conversion layers (23A, 23B) of the nanostructure 10. This makes it possible to reduce optical loss in the core 11 of the nanostructure 10.

[0058] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the present invention. These embodiments can be implemented in various forms other than those described above, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the present invention. These embodiments and their modifications are included in the scope and gist of the present invention, and the inventions described in the claims and their equivalents are also included in the scope and gist of the present invention. [Explanation of symbols]

[0059] 10 Nanostructures 11 Core 11a Outer core part 11b Inner core part 12 Surface layer 20A Photodetector 20B Light emitting element 21 Substrate 22 First electrode layer 23A, 23B Photoelectric conversion layer 24 Second electrode layer

Claims

1. An insulating core portion composed of a multilayer structure whose surface side is coated with a material selected from the group consisting of alumina, silicon nitride, titania, and soda lime glass, or with any one of the group consisting of silica, alumina, silicon nitride, titania, and soda lime glass; A surface layer that covers the core portion, The surface layer is made of MoS 2 It is composed of transition metal dichalcogenides other than The size of the core portion is 100 nm to 1200 nm, The surface layer has a thickness of 5 nm to 50 nm.

2. The transition metal element of the transition metal dichalcogenide includes at least one of Mo, W, Hf, and Zr. The microstructure according to claim 1 .

3. The surface layer is formed with an orientation in which the lamination direction of the transition metal dichalcogenide is perpendicular to the surface of the core portion. The microstructure according to claim 2 .

4. The transition metal element of the transition metal dichalcogenide includes at least one of Nb, V, Ta, and Ti. The microstructure according to claim 1 .

5. The transition metal dichalcogenide is MoS 2 Other than (M, Mo) (Se, S) 2 , M(Se, S) 2 , MSe 2 or M.S. 2 (wherein M is selected from Nb, V, Ta, and Ti) The microstructure according to claim 4 .

6. The chalcogen element of the transition metal dichalcogenide includes at least one of S, Se, and Te. The microstructure according to claim 1 .

7. The refractive index of the core portion is smaller than the refractive index of the surface layer. The microstructure according to claim 1 .

8. The core portion is a multilayer structure having an outer core portion covering a surface of the core portion and an inner core portion adjacent to the inside of the outer core portion, The refractive index of the outer core portion of the multilayer structure is greater than the refractive index of the inner core portion. The microstructure according to claim 1 .

9. The material of the outer core portion is titania and the material of the inner core portion is silica. The microstructure according to claim 8 .

10. A photoelectric conversion element comprising the microstructure according to claim 1 .

11. An insulating core portion composed of a multilayer structure the surface side of which is coated with a material selected from the group consisting of alumina, silicon nitride, titania, and soda lime glass, or with any one of the materials of the group consisting of silica, alumina, silicon nitride, titania, and soda lime glass, and a surface layer coating the core portion, the surface layer being selected from the group consisting of MoS 2 A method for producing a microstructure, the microstructure being composed of a transition metal dichalcogenide other than the above, the core portion having a size of 100 nm to 1200 nm, and the surface layer having a thickness of 5 nm to 50 nm, A step of preparing a first microstructure having an insulating surface; forming a layer containing a transition metal element on a surface of the first microstructure to form a second microstructure; chalcogenizing the layer containing the transition metal element of the second microstructure to form a third microstructure having a surface layer of a transition metal dichalcogenide. A method for manufacturing a microstructure.

12. The transition metal element includes at least one of Mo, W, Hf, Zr, Nb, V, Ta, and Ti. The method for producing a microstructure according to claim 11 .

13. The chalcogen element of the transition metal dichalcogenide includes at least one of S, Se, and Te. The method for producing a minute structure according to claim 11 or 12.

Citation Information

Patent Citations

  • SiO2 / MoS2 core-shell-structure microspheres and preparation method thereof

    CN104694208A

  • Preparation and application of TiO2@MoS2 composite

    CN105148947A

  • Method for preparing 1T@2H-MoS2 / black TiO2

    CN107601557A

  • Oriented polycrystalline thin film of transition metal chalcogenide

    JP1995069782A

  • Light-scattering film and optical device using the same

    JP2006171026A